2020
DOI: 10.1007/s12652-020-02824-z
|View full text |Cite
|
Sign up to set email alerts
|

Employing entropy measures to identify visitors in multi-occupancy environments

Abstract: Human activity recognition (HAR) is used to support older adults to live independently in their own homes. Once activities of daily living (ADL) are recognised, gathered information will be used to identify abnormalities in comparison with the routine activities. Ambient sensors, including occupancy sensors and door entry sensors, are often used to monitor and identify different activities. Most of the current research in HAR focuses on a single-occupant environment when only one person is monitored, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The further approach for the prediction in real time [43] utilizes other methods for own prediction such as HMM [38] , SVD [44] for HAR and ADL with the possibility of using other sensors, e.g. (motion detectors [PIR] and door entry sensors) [42] and using new methods [44] to additive noise canceling in the predicted course of the signal. Moreover, as suggested in [46] , the classification can be further improved by projecting the training instances into the low-dimensional singular subspace; the SVM can train the classification model on it while not violating the privacy requirements for the training data.…”
Section: Discussionmentioning
confidence: 99%
“…The further approach for the prediction in real time [43] utilizes other methods for own prediction such as HMM [38] , SVD [44] for HAR and ADL with the possibility of using other sensors, e.g. (motion detectors [PIR] and door entry sensors) [42] and using new methods [44] to additive noise canceling in the predicted course of the signal. Moreover, as suggested in [46] , the classification can be further improved by projecting the training instances into the low-dimensional singular subspace; the SVM can train the classification model on it while not violating the privacy requirements for the training data.…”
Section: Discussionmentioning
confidence: 99%
“…By analysing PIR sensor data and employing entropy measurements, researchers have established a threshold that indicates the presence of a visitor based on occupancy data's standard deviation and entropy metrics such as Approximate Entropy, Sample Entropy, and Fuzzy Entropy. Many scientific contributions have adopted similar methodologies utilizing PIR sensors to derive occupancy-related insights within indoor environments [20][21][22][23].…”
Section: Related Workmentioning
confidence: 99%
“…Adoption of CSI not only ensures user privacy but also can aggregate multidimensional data associated with an occupant. Some studies have also reported usage of cellular signal for occupancy detection [12]. However, the prime limiting factor with this model is that a user will always require to carry their device in powered on condition.…”
Section: Introductionmentioning
confidence: 99%